Problematika Investasi Pasar Uang Syariah bagi Bank Syariah di Indonesia - Syakur, Riza Rizki Faozan (Asosiasi Pengajar dan Peneliti Hukum Ekonomi Islam Indonesia (APPHEISI), 2022)
The money market has a role to fill the liquidity shortage of a financial institution. Liquidity is an important thing for financial institutions. One of the financial institutions that is growing rapidly and requires money market services is a bank. There are still many mechanisms in the conventional money market that are contrary to the principles of Islamic law. Sharia Bank is a bank which in carrying out its activities is based on the fatwa of the National Sharia Council. So, in using money market instruments it must be in accordance with sharia principles. This article aims to find out the problems in investment activities for Islamic banks through Islamic money market schemes. This study uses library data to be analyzed qualitatively. The results of this study indicate that there are several risks for Islamic banks in using Islamic money market instruments. The thing that must be considered is the time period in the Islamic money market which is not more than one year. In addition, the concept in the Islamic money market is not debt but cooperation.